2006
DOI: 10.1007/s00412-006-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

The diverse roles of transverse filaments of synaptonemal complexes in meiosis

Abstract: In most eukaryotes, homologous chromosomes (homologs) are closely apposed during the prophase of the first meiotic division by a ladderlike proteinaceous structure, the synaptonemal complex (SC) [Fawcett, J Biophys Biochem Cytol 2:403-406, 1956; Moses, J Biophys Biochem Cytol 2: [215][216][217][218] 1956]. SCs consist of two proteinaceous axes, which each support the two sister chromatids of one homolog, and numerous transverse filaments (TFs), which connect the two axes. Organisms that assemble SCs perform m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 134 publications
(205 reference statements)
2
64
0
Order By: Relevance
“…However it has been demonstrated that it is already detectable at late zygonema among prospective CO sites containing MSH4 or RPA foci, and that it occurs at a much higher level in pachytene among MLH1 foci. The colocalization of MSH4 and MLH1 in some early pachytene foci [46] is consistent with positioning of MLH1 foci in two steps, with MLH1 foci being recruited from weakly interfering MSH4 foci [55]. However, because MLH1 and MSH4 foci are distributed differently along the SCs, the factors determining MLH1 focus positions along wild-type SCs might differ from those determining MSH4 focus positions; thus the two levels of interference observed might be temporally and mechanistically distinct.…”
Section: Co Vs Nco and Crossover Interferencesupporting
confidence: 59%
“…However it has been demonstrated that it is already detectable at late zygonema among prospective CO sites containing MSH4 or RPA foci, and that it occurs at a much higher level in pachytene among MLH1 foci. The colocalization of MSH4 and MLH1 in some early pachytene foci [46] is consistent with positioning of MLH1 foci in two steps, with MLH1 foci being recruited from weakly interfering MSH4 foci [55]. However, because MLH1 and MSH4 foci are distributed differently along the SCs, the factors determining MLH1 focus positions along wild-type SCs might differ from those determining MSH4 focus positions; thus the two levels of interference observed might be temporally and mechanistically distinct.…”
Section: Co Vs Nco and Crossover Interferencesupporting
confidence: 59%
“…Identifying proteins residing in the central region of the SC may present a daunting problem. Although TF proteins share a conserved structure consisting of one or more coiled-coil domains and flanking globular domains (15,(45)(46)(47), they are difficult to identify because of a lack of sequence homology among organisms. However, recent demonstrations of characteristic microhomologies (48,49) and insights into the domain signatures of TF proteins (15,45,46,50) make this goal attainable.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, NCO are therefore predicted to be subject to a specific constraint as revealed by the low level of interference between Msh4 foci, whereas no interference could be detected genetically between NCO in S. cerevisiae (Malkova et al 2004). The action of Msh4 both in mammals and yeast could in fact be functionally similar and linked to interference control but operating at different times, and therefore at different stages, along the DSB repair pathway in these organisms (de Boer & Heyting 2006, Fig. 3).…”
Section: Properties Of Nco Productsmentioning
confidence: 98%
“…The number of mouse Msh4 foci goes from 142 to 47 at mid-pachytene (Kneitz et al 2000) where it co-localizes with Mlh1 (SantucciDarmanin et al 2000). Therefore, unlike S. cerevisiae, in mammals the number of Msh4 foci exceeds the number of CO. Msh4 foci are evenly distributed, show a low level of interference and their distribution is clearly different from that of Mlh1, which shows a strong level of interference (de Boer & Heyting 2006). Mutant Msh4 or Msh5 mice show a strong synapsis defect, but have high levels of Rad51 foci (tested in Mhs4j/j mice only), possibly indicating a defect in the processing of recombination intermediates and a failure to establish or maintain stable homologous interactions (de Vries et al 1999, Kneitz et al 2000.…”
Section: Properties Of Nco Productsmentioning
confidence: 99%